Pengaruh Kecukupan Modal, Efisiensi dan Likuiditas Terhadap Rentabilitas di Bank Syariah Milik Pemerintah Indonesia - Sunarya, I Wayan (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
The ratio of financial statements to Islamic banks is one of the determining factors in financial health within the bank itself. For this reason, it is necessary to analyze the influence of capital adequacy, efficiency and liquidity on profitability in the Indonesian state-owned Islamic banks from 2009-2017. This study aims to model the influence of capital adequacy (CAR), Efficiency (BOPO) and Liquidity (FDR) on Rentability (ROA), then analyze the model, and provide forecasting and structural analysis of the model. Therefore, the method used in this study is the analysis of Vector Error Correction Model which is applied to time series data from the level of CAR, BOPO, FDR to ROA. Based on the specification, estimation and examination of the model, the VECM (2) model was obtained as the best model. The results of the model analysis say that there is a long-term and short-term causality relationship between the levels of CAR, BOPO, FDR against ROA. Then, based on forecasting and structural analysis, it can be concluded that the results obtained are accurate.